2003
DOI: 10.1136/ard.2003.008334
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variations in the collagen IX and XI genes are associated with degenerative lumbar spinal stenosis

Abstract: Background: Degenerative lumbar spinal stenosis (LSS) is usually caused by disc herniation or degeneration. Several genetic factors have been implicated in disc disease. Tryptophan alleles in COL9A2 and COL9A3 have been shown to be associated with lumbar disc disease in the Finnish population, and polymorphisms in the vitamin D receptor gene (VDR) (FokI and TaqI), the matrix metalloproteinase-3 gene (MMP-3) and an aggrecan gene (AGC1) VNTR have been reported to be associated with disc degeneration. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 43 publications
7
108
0
1
Order By: Relevance
“…Further evidence for this conclusion is apparent in the Cho mice, which exhibit excess mineralization in the long bones (Seegmiller et al, 1971;Li et al, 1995). Sequence variations in the Col11a1 gene are also associated with osteoarthritis, early-onset osteoarthritis, degenerative lumbar spinal stenosis and cleft palate (Melkoniemi et al, 2003;Noponen-Hietala et al, 2003;Rodriguez et al, 2004;Jakkula et al, 2005). Its association with a variety of common diseases makes Col11a1 an important target for musculoskeletal disease research.…”
Section: Discussionmentioning
confidence: 98%
“…Further evidence for this conclusion is apparent in the Cho mice, which exhibit excess mineralization in the long bones (Seegmiller et al, 1971;Li et al, 1995). Sequence variations in the Col11a1 gene are also associated with osteoarthritis, early-onset osteoarthritis, degenerative lumbar spinal stenosis and cleft palate (Melkoniemi et al, 2003;Noponen-Hietala et al, 2003;Rodriguez et al, 2004;Jakkula et al, 2005). Its association with a variety of common diseases makes Col11a1 an important target for musculoskeletal disease research.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have found familial predisposition to LDD, including early onset sciatica and lumbar disc herniation. In addition, mutations or polymorphisms in several genes have been reported to be associated with either the presence or severity of disc degeneration, including gene coding for collagen IX and XI [2,12,13], aggrecan [9], cartilage intermediate layer protein [18], vitamin D receptor [22], interleukin-1 [19], matrix metalloproteinase-3(MMP-3) [20], tissue inhibitor of metalloproteinase-1(TIMP-1) [21], and cyclooxygenase-2 [21].…”
Section: Introductionmentioning
confidence: 99%
“…3,4,5 These findings suggest that there is a genetic predisposition similar to that which occurs in intervertebral disc degnenraiton. 6,7 In a 2009 study by Kalichman et al, 8 the prevalence of congenital and acquired lumbar stenosis was evaluated radiographically in 191 individuals, averaging 52.6 years of age and with an average BMI of 27.8, who had suffered at least one month of low back pain within a one year timeframe.…”
Section: Introductionmentioning
confidence: 51%